Rancang Bangun Aplikasi Pengolahan Dana PKH Pada Kantor Kepala Desa Dalam Berbasis Web - Selania Selania; Muchlis Muchlis; Sebri Hesinto (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The web-based PKH fund processing application is a web-based application design aimed at distributing Family Hope Program (PKH) aid funds to the village head's office so that they can be distributed quickly and accurately. This application has features that include data collection, aid recipients, announcements or information on disbursement of aid regarding the Harapan Family Program (PKH). The advantages of using this PKH fund processing information system application are minimizing the risk of data errors and optimizing the time and resources involved in the PKH fund processing process.